State-of-the-art techniques in radiation dosimetry – technological segments and applications (Brazilian Journal of Radiation Sciences (BJRS), 2021)
This work presents a study based on patent filings as a resource for identifying technological trends in the field of radiation dosimetry for a view of the state-of-the- art techniques, in addition to the main actors involved and patent search process in the area of ionizing radiation. It aimed to make an analysis of patent portfolios to outline an application scenario for the knowledge developed in the area. It was carried out through consultation using the Questel Orbit search and analysis system having the word “dosimetry” and its similars, by semantic similarity, for the years between 1999-2019. The results are discussed regarding the main deposits, depositors, time evolution, technological segments and geographic coverage. They point out that companies that operate simultaneously in the area of energy power generation and medical applications have a significant contribution to the production of patents. Studies focused on the development of dosimetric systems move several technological segments, mainly environmental and medical technology.